Sustained and controlled delivery of doxorubicin from an in-situ setting biphasic hydroxyapatite carrier for local treatment of a highly proliferative human osteosarcoma. (1st September 2021) - Liu, Yang; Raina, Deepak Bushan; Sebastian, Sujeesh; Nagesh, Harshitha; Isaksson, Hanna; Engellau, Jacob; Lidgren, Lars; Tägil, Magnus
Abstract: Doxorubicin (DOX) is a cornerstone drug in the treatment of osteosarcoma. However, achieving sufficient concentration in the tumor tissue after systemic administration with few side effects has been a challenge. Even with the most advanced nanotechnology approaches, less than 5% of the total administered drug gets delivered to the target site. Alternatives to increase the local concentration of DOX within the tumor using improved drug delivery methods are needed. In this study, we evaluate a clinically approved calcium sulfate/hydroxyapatite (CaS/HA) carrier, both in-vitro and in-vivo, for local, sustained and controlled delivery of DOX to improve osteosarcoma treatment. In-vitro drug release studies indicated that nearly 28% and 36% of the loaded drug was released over a period of 4-weeks at physiological pH (7.4) and acidic pH (5), respectively. About 63% of the drug had been released after 4-weeks in-vivo. The efficacy of the released drug from the CaS/HA material was verified on two human osteosarcoma cell lines MG-63 and 143B. It was demonstrated that the released drug fractions functioned the same way as the free drug without impacting its efficacy. Finally, the carrier system with DOX was assessed using two clinically relevant human osteosarcoma xenograft models. Compared to no treatment or the clinical standard of care with systemic DOX administration, the delivery of DOX using a CaS/HA biomaterial could significantly hinder tumor progression by inhibiting angiogenesis and cell proliferation. Our results indicate that a clinically approved CaS/HA biomaterial containing cytostatics could potentially be used for the local treatment of osteosarcoma. Statement of significance: The triad of doxorubicin (DOX), methotrexate and cisplatin has routinely been used for the treatment of osteosarcoma. These drugs dramatically improved the prognosis, but 45-55% of the patients respond poorly to the treatment with low 5-year survival. In the present study, we repurpose the cornerstone drug DOX by embedding it in a calcium sulfate/hydroxyapatite (CaS/HA) biomaterial, ensuring a spatio-temporal drug release and a hypothetically higher and longer lasting intra-tumoral concentration of DOX. This delivery system could dramatically hinder the progression of a highly aggressive osteosarcoma compared to systemic administration, by inhibiting angiogenesis and cell proliferation. Our data show an efficient method for supplementary osteosarcoma treatment with possible rapid translational potential due to clinically approved constituents. Graphical abstract: Image, graphical abstract